E‐Commerce Enablers and Barriers in Tanzanian Small and Medium Enterprises. Issue 1 (5th December 2017) - Kabanda, Salah K.; Brown, Irwin
Abstract: The purpose of this study is to identify enablers of and barriers to E‐Commerce in Tanzanian small and medium enterprises (SMEs). Tanzania is classified as a least developed country (LDC) and has received relatively little research attention with respect to E‐Commerce in the SME sector. The study is qualitative in nature and a set of semi‐structured interviews were used to collect data. 32 SMEs were interviewed. A thematic analysis approach was used for reporting SME's experiences, perspectives, and meanings, whilst examining the ways in which events, realities, meanings, and experiences come about. The study unearthed contextual understanding of E‐Commerce and the challenges faced by Tanzanian SMEs. Factors perceived to be conducive for E‐Commerce, include the availability of business resources, specifically business relationships with ICT foreign companies; top management support; the use of mobile technology for interactive and transactive purposes with consumers and suppliers; and the strategic use of mobile phones to avoid ICT‐related challenges such as those associated with fixed line telephone and Internet‐enabled desktop computing.